Short-Term Exposure to Ambient Air Pollution and Biomarkers of Systemic Inflammation: The Framingham Heart Study. Issue 9 (September 2017) - Li, Wenyuan; Dorans, Kirsten S.; Wilker, Elissa H.; Rice, Mary B.; Ljungman, Petter L.; Schwartz, Joel D.; Coull, Brent A.; Koutrakis, Petros; Gold, Diane R.; Keaney, John F.; Vasan, Ramachandran S.; Benjamin, Emelia J.; et al.
Abstract : Objective—: The objective of this study is to examine associations between short-term exposure to ambient air pollution and circulating biomarkers of systemic inflammation in participants from the Framingham Offspring and Third Generation cohorts in the greater Boston area. Approach and Results—: We included 3996 noncurrent smoking participants (mean age, 53.6 years; 54% women) who lived within 50 km from a central air pollution monitoring site in Boston, MA, and calculated the 1- to 7-day moving averages of fine particulate matter (diameter<2.5 µm), black carbon, sulfate, nitrogen oxides, and ozone before the examination visits. We used linear mixed effects models for C-reactive protein and tumor necrosis factor receptor 2, which were measured up to twice for each participant; we used linear regression models for interleukin-6, fibrinogen, and tumor necrosis factor α, which were measured once. We adjusted for demographics, socioeconomic position, lifestyle, time, and weather. The 3- to 7-day moving averages of fine particulate matter (diameter<2.5 µm) and sulfate were positively associated with C-reactive protein concentrations. A 5 µg/m 3 higher 5-day moving average fine particulate matter (diameter<2.5 µm) was associated with 4.2% (95% confidence interval: 0.8, 7.6) higher circulating C-reactive protein. Positive associations were also observed for nitrogen oxides with interleukin-6 and for black carbon, sulfate, and ozone with tumor necrosis factor receptor 2. However, black carbon, sulfate, and nitrogen oxides were negatively associated with fibrinogen, and sulfate was negatively associated with tumor necrosis factor α. Conclusions—: Higher short-term exposure to relatively low levels of ambient air pollution was associated with higher levels of C-reactive protein, interleukin-6, and tumor necrosis factor receptor 2 but not fibrinogen or tumor necrosis factor α in individuals residing in the greater Boston area. Abstract : Supplemental Digital Content is available in the text.